Modeling and initial growth mode of ultrathin film on the basis of electrical conductivity of substrate - Song, SK; Koh, SK; Lee, DY; Song, KM; Baik, HK (JAPAN SOC APPLIED PHYSICS, 2004)
A model for the electrical conductance of a semiconductive substrate with an average thickness is proposed for a region of initial growth before the appearance of a tunneling effect. Based on this model, we propose 6 different growth modes according to the film thickness, measuring in stitu electrical conductivity. As the film thickness increased, the island size was constant and then increased, while the number of islands first increased and then decreased. The proposed model may be useful for in situ study of the growth of ultrathin films prior to the onset of tunneling conductance.
Keywords: INDIUM TIN OXIDE; THIN-FILMS; IN-SITU; GROWING FILMS; METAL-FILMS; DEPOSITION; BEAM; ELLIPSOMETRY; SPECTROSCOPY; TRANSITION